Three Active Learning Strategies to Address Mixed Student Epistemologies and Promote Conceptual Change - Kalman, Calvin S.; Lattery, Mark J. (Frontiers in ICT, 2018)
Novice science learners or introductory science students vary greatly in their understanding of the nature of science. For example, many students do not conceive of scientific knowledge as a highly ordered, coherent, knowledge structure that contains a set of interrelated ideas. Such a framework enables the learner to relate new material to prior knowledge and, if warranted, assimilate the new material within the framework. Many students have strong beliefs that knowledge is conveyed by authorities, such as the instructor and the textbook. Also many student’s own knowledge structure is fragmented or “in pieces”, as described by diSessa. Fortunately, this portrayal is not valid for all students.. Many other students enter the classroom with productive intellectual values and possess, or can quickly develop with little prompting, alternative and coherent conceptions that conflict with target ideas. These students are able to relate new material to prior knowledge and, if warranted, assimilate new material into pre-existing conceptions. The challenge of contemporary science education reform is therefore to address the diverse needs of a “mixed student epistemology” classroom. In this paper we review three instructional strategies that show promise to address this challenge in the context of an introductory physics classroom: (1) the Reflective Writing and Labatorial interventions of Kalman et. al., (2) the Conceptual Conflict Collaborative Group and Critique approaches of Kalman & Rohar, and (3) the integrated Elicit-and-Challenge and Bridging Technique strategies of Lattery. Each approach stresses the need for students to critically examine their own ideas in the in relation to target course ideas and discuss their ideas with peers. The second and third approaches emphasize the important role of the history and philosophy of science in science teaching. The aim of such efforts is not only to convey subject-matter content knowledge, but also to shape the student mindset, metacognitive practice, and understanding of the nature of science.